Effects of S-adenosylhomocysteine and analogs on Epstein-Barr virus-induced transformation, expression of the Epstein-Barr virus capsid antigen, and methylation of Epstein-Barr virus DNA. - Long, W K (1987)
S-Adenosylhomocysteine was found to have no effect on Epstein-Barr virus-induced transformation of B-lymphocytes and to stimulate viral capsid antigen expression only slightly in the FF41-1 cell line. In contrast, the S-adenosylhomocysteine analogs sinefungin and S-isobutyladenosine inhibited Epstein-Barr virus transformation and induced a significant increase in the numbers of cells expressing the viral capsid antigen. An inverse relationship between levels of viral DNA methylation and gene expression was demonstrated.